2013
DOI: 10.1002/grl.50262
|View full text |Cite
|
Sign up to set email alerts
|

Are climatic or land cover changes the dominant cause of runoff trends in the Upper Mississippi River Basin?

Abstract: [1] The Upper Mississippi River Basin (UMRB) has experienced a remarkable agricultural extensification since the mid-1800s. Hydroclimatological monitoring in the 20th century also reveals positive annual precipitation and runoff trends in the UMRB. While several studies have proposed land use/land cover (LULC) change as the primary cause of runoff increase, little is known about the dominant controls of hydrologic change in the UMRB. We used a macroscale hydrology model to assess the hydrologic implications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 38 publications
9
98
1
Order By: Relevance
“…The average streamflow at the outlet station (#05587450) of UMRB for the period assessed in this study (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) slightly increased from 3800.2 m 3 /s to 4041.3 m 3 /s. This is consistent with several studies that have shown an increasing trend in the annual streamflow in the UMRB since the 1940s [14,15,40,41]. However, freshwater provisioning is not necessarily improved with the increased streamflow.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The average streamflow at the outlet station (#05587450) of UMRB for the period assessed in this study (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) slightly increased from 3800.2 m 3 /s to 4041.3 m 3 /s. This is consistent with several studies that have shown an increasing trend in the annual streamflow in the UMRB since the 1940s [14,15,40,41]. However, freshwater provisioning is not necessarily improved with the increased streamflow.…”
Section: Discussionsupporting
confidence: 91%
“…The river water is primarily used for drinking purposes and industrial applications [21][22][23]. Despite its ecological significance, the conservation status and the ecological integrity of UMRB have been heavily impacted due to various anthropogenic activities, including land use changes to support extensive agricultural production, and hydrologic modification of rivers for navigation and flood control [14,18,19]. …”
Section: The Upper Mississippi River Basinmentioning
confidence: 99%
See 2 more Smart Citations
“…The domain includes the Missouri, Upper Mississippi and Ohio River basins ( mostly rainfed over the Upper Mississippi, Ohio and Northern Missouri river basins. Natural flow has been shown, at least over the Upper Mississippi river basin (Frans et al, 2013;Mishra et al, 2010), to be more sensitive to climate change than to land use change. However, this region represents many crosscutting issues on climate, energy, land use, and water, including water quality.…”
Section: Domainmentioning
confidence: 99%